Performance Analysis of H-bridge and T-Bridge Multilevel Inverters for Harmonics Reduction - S. Usha; C. Subramani; A. Geetha (Institute of Advanced Engineering and Science, 2018)
This paper deals with the design of cascaded 11 level H- bridge inverter. It includes a comparison between the 11 level H-bridge and T-bridge multilevel inverter. The cascaded inverter of higher level is a very effective and practical solution for reduction of total harmonic distortion (THD).These cascaded multilevel inverter can be used for higher voltage applications with more stability. As the level is increased the output waveform becomes more sinusoidal in nature. The inverter is designed using multicarrier sinusoidal pulse width modulation technique for generating triggering pulses for the semiconductor switches used in the device. Through this paper it will be proved that a cascaded multilevel H-bridge topology has higher efficiency than a T-bridge inverter, as whichever source input voltage is provided since input is equal to the output voltage. In T-bridge inverter, the output obtained is half of the applied input, so efficiency is just half as compared to H-bridge. The output waveform is distorted and has higher THD. The simulation is performed using MATLAB /Simulink 2013 software.